2020
DOI: 10.1002/pa.2206
|View full text |Cite
|
Sign up to set email alerts
|

Policy response to the economic challenge from COVID ‐19 in India: A qualitative enquiry

Abstract: The recent COVID-19 pandemic has not only resulted in the loss of human lives but also distressed economies. The impact of this crisis is even higher in emerging economies like India due to already slowing growth rates, poor health infrastructure, and a significant population living in extreme poverty. While the government is taking measures to handle this crisis, nobody can be sure if these measures are adequate, as this will depend on how soon the spread of the virus is contained in the country. However, und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 19 publications
0
55
0
2
Order By: Relevance
“…The lockdown imposition in all parts of the world led to a significant drop among the stock market indices points. The stock market returns exhibit higher volatility during the sample period, which was triggered by the COVID-19's multiple impacts, including nationwide lockdown, higher unemployment rates, lower consumption levels, migration of workers, restricted demand and supply chains, and the distressed financial markets ( Sharma et al., 2020 ). Stock markets are leading variables in the economy ( Harvey, 1989 ), and the higher volatility and fluctuations on major stock market returns during the pandemic outbreak document the expected continuous downfall in the national and international financial markets.…”
Section: Discussionmentioning
confidence: 99%
“…The lockdown imposition in all parts of the world led to a significant drop among the stock market indices points. The stock market returns exhibit higher volatility during the sample period, which was triggered by the COVID-19's multiple impacts, including nationwide lockdown, higher unemployment rates, lower consumption levels, migration of workers, restricted demand and supply chains, and the distressed financial markets ( Sharma et al., 2020 ). Stock markets are leading variables in the economy ( Harvey, 1989 ), and the higher volatility and fluctuations on major stock market returns during the pandemic outbreak document the expected continuous downfall in the national and international financial markets.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 has impacted the global economy significantly including India. Few of the recent researches have tried to analyze the implications of COVID-19 pandemics on agricultural productions and supply chain globally (Pu & Zhong, 2020;Kumar, Padhee, & Kumar, 2020;Gillespie, 2020;Galanakis, 2020;Singh & Neog, 2020;Solomon, Pratap, & Swapna, 2020;Weersink, von Massow, & McDougall, 2020;Sharma, Talan, & Jain, 2020;Zhang et al, 2020). Pu and Zhong (2020) argued that unreasonable restrictions would block the outflow channels of agricultural products, hinder necessary production inputs, destroy production cycles, and finally undermine production capacity and suggested that there is a need to ensure effective logistics for agricultural products, ensure effective supply of critical inputs, provide various supports to agricultural production and farmers and make use of innovative methods to promote sales such as e-tailing.…”
Section: Introductionmentioning
confidence: 99%
“…This lockdown was subsequently extended for a week, then for 21 days and finally until 3rd May 2020 to contain the spread of COVID-19. India declared COVID-19 a "notified disaster" under the Disaster Management Act, 2005 (Sharma et al 2020). Extended lockdown and other social distancing measures imposed to curb the pandemic made women more vulnerable to domestic violence.…”
Section: Domestic Violence In India During Covid-19mentioning
confidence: 99%